Partyjni dysydenci, czyli krótka historia myśli (anty)socjalistycznej I sekretarza KW PZPR w Poznaniu, Edwarda Skrzypczaka: studium przypadku - Bielanowska, Judyta (Komunizm: System - Ludzie - Dokumentacja, 2023)
The political biography of Edward Skrzypczak, former First Secretary of the Polish United Workers’ Party in Poznań in 1981–1982, is the biography of a party dignitary whose fidelity to the ideals of socialism was the reason for his dismissal from his position. This is the story of a man who, despite belonging to the PZPR, was able to win over representatives of the democratic opposition around him, earning their trust and respect. The political fate of Edward Skrzypczak is also a story about the need to make the most important choices and make decisions in the face of formal membership in the Party, marked by the distortions of his own ideology, and at the same time the desire to revise the ossified forms of bureaucratic organization and to meet the needs of the society, which for the first secretary of the Provincial Committee of the Polish United Workers’ Party in Poznań always was the highest value, which was confirmed after the introduction of martial law, when in an exceptionally difficult situation for most Poles, Edward Skrzypczak’s personality traits became an invaluable help for the interned, who could count on the effective help of the 1st secretary. Contrary to all circumstances, he remained forever faithful to socialist ideals, loyal to General Jaruzelski and approving his decision to introduce martial law. After the socio-political changes in 1989, Edward Skrzypczak still maintains the socialist system of values